ANALSIS PENCATATAN PEMBAYARAN PAJAK PENGHASILAN PADA USAHA MIKRO KECIL MENENGAH DI WILAYAH KOTA SEMARANG - Djoko Wahjudi; Arief Himawan (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2014)
This study aims to determine the condition of payment of income tax of SMEs in the Region of Semarang, how therecording of tax payments and whether taking notes in case of underpayment or overpayment. The population in this studyare all taxpayers SMEs located in the County of Semarang. While the sample studied through primary data by distributingquestionnaires to be addressed, direct interviews and secondary data through the office of the Department of Cooperativesand SMEs in Semarang. The sampling technique used is convenience sampling. Data analysis was performed usingdeskretif qualitative analysis to see how the map SMEs in the Region of Semarang on the condition of their businessactivities, capital and liabilities that can be known perpajakanya deficiency or excess. The research results in graphicalform shows that the conditions of tax payments made by the respondents most of the information obtained from pertugastaxes, the taxpayer has to pay taxes on time, taxpayers will determine tax rates and the calculation. Results show that theknowledge of the taxpayer, an understanding of the tax laws and benefits are fulfilled contributed to the reporting oftaxation, and SMEs have experienced an overpayment or underpayment in tax payments, SMEs also make adjustments incase of overpayment or underpayment although the adjustment is done not in accordance with Financial AccountingStandards for Small and Medium Enterprises.Keywords: UMKM, tax payment, registration tax, tax adjustment.